1982
DOI: 10.1203/00006450-198205000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of β-Adrenergic Receptors in the Rat Lung: Effects of Hypothyroidism

Abstract: ((f)-[12611HYP). Binding capacity (B, , ) for (-)-I3H]DHA increased progressively from 46 + 7 on day 18 of gestation to 510 2 70 femt~moles*mg-~ protein (mean + S.D.) on postnatal day 28, at which time adult B, , was attained. An increase in (-)-i3HI DHA binding capacity of the lung was observed between postnatal days 15 and 28, during the known period of increased thyroid gland secretory activity, serum triiodothyronine (T3), and thyroxine (T4) concentrations in the rat. We therefore studied lung /?-adrener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The changes in Bmax reported here in response to hormone infusion were significantly greater than those reported in control fetal lambs during the same period of gestation. In the rabbit fetus, glucocorticoids increase the number of P-receptor binding sites (4), whereas in the rat fetus hypothyroidism decreases the number of binding sites (5). The lack of effect of corticosteroids alone on P-receptor binding capacity in the fetal lamb lung may be due either to a species difference or to the physiological concentrations of cortisol used herein in comparison with the pharmacological concentrations used in other systems (2).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The changes in Bmax reported here in response to hormone infusion were significantly greater than those reported in control fetal lambs during the same period of gestation. In the rabbit fetus, glucocorticoids increase the number of P-receptor binding sites (4), whereas in the rat fetus hypothyroidism decreases the number of binding sites (5). The lack of effect of corticosteroids alone on P-receptor binding capacity in the fetal lamb lung may be due either to a species difference or to the physiological concentrations of cortisol used herein in comparison with the pharmacological concentrations used in other systems (2).…”
Section: Discussionmentioning
confidence: 53%
“…Glucocorticoids and thyroid hormones act at different points in the pathways of surfactant phospholipid synthesis (2), whereas (3-agonists stimulate surfactant release and also regulate the production of fetal lung liquid (3). The maximal binding capacity of fetal lung preceptors is regulated by glucocorticoids (4) and thyroid hormones (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other hormonal factors that normally increase in rats around the normal time of weaning include growth hormone (32) and somatomedin C (33). P-Adrenergic receptors in the rat lung markedly increase between d 15-28, and this change in receptor density is related to the normal rise in serum T3 levels at this time (34). The rise in serum growth hormone levels at approximately 20 d of age is also dependent upon the normal rise of T3 and the rise in glucocorticoid hormones at this time (35).…”
Section: Discussionmentioning
confidence: 80%
“…Glucocorticoids have been reported to increase the @-receptor binding capacity of fetal rabbit lung (19), whereas hypothyroidism was shown to inhibit preceptor binding capacity in fetal rat lung (20). In addition, Maniscalco et al (14) and Warburton et al (21) have reported synergistic effects of glucocorticoid and thyroid hormones on Preceptor binding capacity in fetal rabbit lung explants in culture and in fetal lamb lung, respectively.…”
Section: Discussionmentioning
confidence: 93%